Penerimaan diri remaja putri akhir: Adakah peranan citra tubuh? - Uyun, Jauharotul; Matulessy, Andik; Rina, Amherstia Pasca (JIWA: Jurnal Psikologi Indonesia, 2023)
Body image is a subjective picture of a person's body appearance, especially judgments from others. These judgments, which form good or bad perceptions that will lead to individual self-acceptance. While self-acceptance is something that must be owned by every individual. If a person has a positive assessment of his body, then that person will accept himself. Which means accepting all the shortcomings and advantages possessed. The benefits of body image and self-acceptance are so that individuals can be more accepting and peaceful to whatever conditions exist in themselves. The analysis technique used is the product moment correlation technique. The sampling technique in this study used simple random sampling. The subjects in this study were 205 female students of SMK N 1 Bojonegoro aged 18-21 years. The instruments used are the body image scale which refers to the MBSRQ_AS scale and the self-acceptance scale which refers to Harlock's theory. The data analysis used is product moment correlation analysis with the help of SPSS version 20.0 for windows. The results of this study showed that the results of the correlation test showed a significant positive relationship between body image and self-acceptance in late adolescent girls. Citra tubuh merupakan suatu gambaran subjektif tentang penampilan tubuh seseorang khususnya penilaian dari orang lain. Penilaian tersebut, yang membentuk persepsi-persepsi baik atau buruk yang akan mengarah pada penerimaan diri individu. Sedangkan penerimaan diri meruapakan sesuatu harus dimiliki oleh setiap individu. Apabila seseorang memiliki penilaian positif tentang tubuh yang dimiliki, maka seseorang tersebut akan menerima dirinya. Yang artinya menerima segala kekurangan serta kelebihan yang dimiliki. Manfaat citra tubuh dan penerimaan diri adalah agar individu dapat lebih menerima dan damai terhadap kondisi apapun yang ada pada dirinya.Teknik analisis yang digunakan yang digunakan adalah teknik korelasi product moment. Teknik sampling dalam penelitian ini menggunakan simple random sampling. Subjek dalam penelitian ini adalah 205 siswi SMK N 1 Bojonegoro yang berusia 18-21 tahun. Instrumen yang digunakan adalah skala citra tubuh yang mengacu pada skala MBSRQ_AS dan skala penerimaan diri yang mengacu pada teori Harlock. Analisis data yang digunakan adalah analisis korelasi product moment dengan bantuan SPSS versi 20.0 for windows. Hasil penelitian ini menunjukkan hasil uji korelasi terdapat hubungan positif yang signifikan antara citra tubuh dengan penerimaan diri pada remaja putri akhir.